Understanding Electrolytes: 15 Interactive Teaching Cases - Rajeev Raghavan (Association of American Medical Colleges, 2013)
Abstract Introduction Students in health care professions have traditionally experienced apprehension and difficulty when interpreting a single or pattern of abnormal electrolytes. Furthermore, medical educators in the disciplines of internal medicine, surgery, and nephrology have struggled to find a fun, interactive way to teach this material. This educational resource is a unique, interactive curriculum with two objectives: (1) learn how to interpret body fluid electrolytes via an enjoyable and unique method, and (2) reduce learner anxiety when confronted with abnormal laboratory values. The primary audience includes medical or allied health students, medical or surgical residents, and physicians in practice. Methods There are 15 fictional cases in which the learner is given only a set of electrolytes (serum and/or urine), without any clinical history or physical exam findings. Each case corresponds to a different patient. The learner is asked to work through the abnormal laboratory findings to reach a single unifying diagnosis. This process teaches the learner how to interpret single abnormal lab values, and recognize how a pattern of abnormal values represents a specific disease state. The 15 cases encompass a wide variety of common medical or surgical cases with electrolyte disturbances. These include, but are not limited to: congestive heart failure, diabetic ketoacidosis, renal tubular acidosis, metabolic alkalosis, hypokalemia, and toxic alcohol ingestions. The facilitator is usually a physician (internal medicine, general surgery, or nephrology), or allied health/nursing professional. The cases and correct answers are provided in an instructor's guide and answer guide, respectively. The student is typically given this answer guide as a reference at the completion of the module. Although it can take several hours to review each case in the necessary detail, it is typically used as a 1-hour classroom session; during which time six cases are covered and discussed. Results This resource is extremely effective. It has been tested on second-year medical students at our institution during their internal medicine rotation. Over an 18-month period (105 students), the average score out of 7.0 for the query "I am more confident in my ability to interpret electrolytes." was 6.4; and for "I learned something new in this lecture." was 6.7. Selected comments include: "Great to work through example rather than lecture style," "One of the best lectures in medicine. Extremely worthwhile," and "Well planned and logical, very clinically applicable." At the end of the module, over 95% of surveyed students report less anxiety when confronted with major electrolyte disturbances (e.g. hyponatremia). Similarly, over 90% of students enjoyed the curriculum and gained new knowledge. Discussion Students traditionally experience difficulty and apprehension when interpreting a single or pattern of abnormal electrolytes, but this series of cases helps them build their confidence and skill.